The occurrence of rare corsac fox (Vulpes corsac) in Iran is mainly determined by prey presence and land use. (June 2021) - Ahmadpour, Mohsen; Shokri, Shirko; Varasteh-Moradi, Hossein; Waltert, Matthias; Khorozyan, Igor; Soofi, Mahmood
Abstract: Many species occur on unprotected lands, but continuing human pressure makes them rare especially outside protected areas (PAs). The corsac fox is a common predator in Central Asia, but rare in Iran and its conservation status is poorly understood. We aimed to assess its distribution in relation to natural and human factors. Using 31 occurrence records of corsac and 272 of its main prey species, we used maximum entropy modeling to determine the key factors affecting corsac distribution, find priority conservation areas and evaluate the role of PAs. We found that corsac presence was strongly inversely associated with the distance to gerbil burrows, land use and distance to PA, followed by precipitation, vegetation types, distance to villages, road density and distance to river. Corsacs mostly occurred outside PAs, with highly suitable habitats covering only 6.3% of the study area and one PA covering 11% of highly suitable habitats. Our results suggest that, in Iran, the corsac may tolerate some landscape modification, but its distribution is strongly related to its main prey and low intensity of land use. We suggest to expand the existing no-hunting areas (unclassified by the IUCN) and upgrade them to better managed PAs compliant with international standards. Highlights: Corsac fox appears to tolerate some landscape changes, but is strongly linked to its main prey and low intensity of land use. Corsacs occur mostly outside protected areas suggesting to protect them under better conservation regimes . Only 6.3% of the arid lands of Golestan Province in Iran are highly suitable for corsac fox. There is only one protected area covering 11% of highly suitable habitats for corsac.